Nutritive Value of Some Agro–Industrial by–Products as Supplement to Guinea Grass (Panicum Maximum) By Sokoto Gudali Calf - Bamigboye, Funmilayo O; Igbekoyi, A. J; Babayemi, O. J (Journal of Nutrients, 2014)
Supplementation value of some agro–industrial by–products was assessed by 12 Sokoto Gudali calves in a Completely Randomized Design. Four test diets were formulated: Palm Kernel Cake (PKC), Brewer’s Dried Grain (BDG), Wheat Offal (WO) and combinations of PKC + BDG + WO based diets while Guinea grass was fed as the basal diet. Diet A (33.25 % PKC), diet B (33.25 % BDG), diet C (33.25 % WO) and diet D (11.08 % PKC + 11.08 % BDG + 11.08 % WO) were included in the formulated diets. The proximate composition of the diets and performance characteristics of calves on these diets were assessed using standard procedures. Diet D was observed to have the highest CP, CF and ether extract (28.3, 34.0 and 20.0 % respectively) while diet C followed a direct inverse trend of this in terms of DM, CP and CF (55.8, 22.6 and 23.0 % respectively). Results also showed that there were not significant differences among the treatments in final weight, weight gain, daily weight gain and the feed conversion ratio but diet A was significantly different (P < 0.05) from other treatments in feed intake. It is concluded that brewer’s dried grains and wheat offal can be interchangeably used as well as combinations of the two in addition to the palm kernel cake as supplement to grass by Sokoto Gudali cattle for production and management.